A Rare Case of Acute Generalized Exanthematous Pustulosis in a Filipino Female Pediatric Patient with Systemic Lupus Erythematosus - Mendoza, Jr., Manuel; Macaraeg, Maritess; Tuazon, Camelia Faye (Philippine Journal of Allergy, Asthma and Immunology, 2025)
Acute generalized exanthematous pustulosis (AGEP) is a rare, febrile drug eruption characterized by non-follicular pustules and systemic involvement. Its features may overlap with systemic lupus erythematosus (SLE), complicating diagnosis and management. This study reports the first documented pediatric case of this complex disease phenomenon. An 18-year-old Filipino female with newly diagnosed SLE on hydroxychloroquine presented with diffuse non-follicular pustules and fever after the initiation of azithromycin for upper respiratory tract infection. Histopathology examination revealed subcorneal pustules, which, together with clinical and dermoscopic findings, supported the clinical diagnosis of Definitive AGEP (EuroSCAR Score 11). Both identified high-risk drugs, hydroxychloroquine and azithromycin, were discontinued. Following drug withdrawal, corticosteroid, and supportive care, her clinical condition subsequently improved. This report highlights the diagnostic challenge between AGEP and SLE. An interleukin-8-mediated mechanism appears to play a central role in bridging the pathogenesis of both conditions. Despite controversies, corticosteroids have proven to be an effective adjunct in the management of AGEP, while controlling the underlying SLE.